ANALISIS VARIABEL KEUANGAN SEBAGAI PREDIKTOR BETA SAHAM - Nova, I Kadek Satria; Ramantha, I Wayan; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
There are certain risks and returns that may appear and need to be considered by investors in capital market. The two types of risk are systematic risk and unsystematic risk. Systematic risk is also called as beta since it is the measurement of systematic risk. Based on previous researches, it was obtained that financial variables including financial leverage, liquidity, asset growth, profitability and dividend payout ratio had inconsistent results as stock beta predictor. Therefore the researcher is motivated to examine these financial variables as the stock beta predictor. Technique of data analysis in this research are of test of classic assumptions and test of hyphotesis that used multiple regression analysis. The research result: 1) financial leverage cannot  affect stock beta because. 2) Liquidity has negative significant effect to stock beta. 3) Asset growth cannot affect stock beta. 4) Profitability  has positive significant effect to stock beta. 5) Dividend payout ratio cannot affect to stock beta.
Keywords: stock beta, financial leverage, likuiditas, asset growth, profitabilitas, dividend payout ratio